2018
DOI: 10.1111/jfbc.12571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of peptide characteristics on their stability, intestinal transport, and in vitro bioavailability: A review

Abstract: In recent years, large amounts of peptides have been purified and characterized from food protein hydrolysates. Many of these peptides have been demonstrated to be of potential application as health-improving ingredients against plenty of disease conditions, such as cancer, inflammation, and cardiovascular disease. The real efficacy of functional application of these peptides depends on their stability, transport, and bioavailability in target tissues, which in turn depends on the peptides characteristics. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 46 publications
0
85
1
1
Order By: Relevance
“…This route is preferred by hydrophilic low‐molecular‐weight peptides released during protein digestion (Wang & Li, ). Proteins/peptides with molecular weight >700 Da exhibit low bioavailability, but polypeptides with high conformational flexibility can diffuse through the tight junctions (Wang et al ., ). On the other hand, enhanced flexibility of cyclic peptide drugs reduced their oral bioavailability.…”
Section: Digestion and Absorption Of Protein And Peptidesmentioning
confidence: 97%
“…This route is preferred by hydrophilic low‐molecular‐weight peptides released during protein digestion (Wang & Li, ). Proteins/peptides with molecular weight >700 Da exhibit low bioavailability, but polypeptides with high conformational flexibility can diffuse through the tight junctions (Wang et al ., ). On the other hand, enhanced flexibility of cyclic peptide drugs reduced their oral bioavailability.…”
Section: Digestion and Absorption Of Protein And Peptidesmentioning
confidence: 97%
“…However, another study reported that peptides with high molecular weights had better iron binding capacity [ 67 ]. This type of peptide promoted mineral uptake in cultured intestinal cells [ 68 ] and those with low molecular weights were more stable during in vitro gastrointestinal digestion [ 69 ]. In addition, smaller peptides with a higher charge density have a stronger affinity towards metals [ 66 ].…”
Section: Structure–activity Relationship and Stability Of Peptide–mentioning
confidence: 99%
“…It is stated that > 3-kDa peptides are more likely to be degraded by gastrointestinal proteases than < 3-kDa peptides, but this behavior depends also on the amino acid sequence of the proteins. The terminal residues are an important factor determining their resistance [178].…”
Section: Bioavailability In Vitromentioning
confidence: 99%
“…This process depends mainly on their size and hydrophobicity. Hence, intact peptide absorption can occur via different mechanisms, from the enterocyte into the portal circulation, described below [175,178].…”
Section: Bioavailability In Vitromentioning
confidence: 99%